Peran Pemerintah Desa Dalam Mengelola Lapangan Kerja di Desa Mlirip Kec. Jetis - Muhaimin, Hikmah; Aprisal F. L, Muchammad; Yuliasari , Iqma; Nur Hidayah, Nindy Lulu; Tianlie, Nabella Rizka (Jurnal Identitas, 2022)
Government in labor is a very important factor. State intervention ensures fair labor laws in industry or labor relations. According to the Industrial Relations Law, the system of relations between the parties in the process of producing goods and services, consisting of elements of employers, workers, or workers and the government, indicates an intervention in industrial relations. update. Outsourcing work is one of the by-products of business process reengineering (BPR). BPR is not just a recovery, it is a fundamental change in the way businesses operate. BPR is a game changer for how organizations operate, and traditional approaches of continuous improvement processes take a long time. BPR was implemented in response to the world's economic growth and rapid technological development to facilitate competition in a highly competitive global era. In the field of labor, large-scale outsourcing is defined as the use of labor by a company to produce or perform work for an employer. The purpose of industrial relations is to improve the productivity and welfare of workers and employers. There are two ways to resolve labor relations. 7 Labor disputes Industrial relations disputes, which is the settlement of disputes due to the absence of mutual understanding between employers or employers' organizations and workers' organizations or trade unions. Work relations, working conditions and/or relations related to working conditions. The purpose of industrial relations is to improve the productivity and welfare of workers, and industrial relations can be resolved in two ways. In other words, it is a judicial review procedure in the labor court. Between employers or employers' unions and workers' unions or cooperatives due to a lack of mutual understanding about work relations, working conditions and/or relations relating to working conditions.